Causes for professionalization in national sport federations in Switzerland: a multiple-case study - Ruoranen, K.; Clausen, J.; Nagel, S.; Lang, G.; Klenk, C.; Giauque, D.; Bayle, E.; Schlesinger, T. (Current Issues in Sport Science, 2018)
Aim and design: This study explores causes for professionalization in Swiss national sport federations (NSFs). We conducted a multiple-case study employing a qualitative approach with interviews and documents from seven NSFs. A three-level framework guided the analysis in distinguishing NSF endogenous causes, and causes in their external and internal environment.